Respuesta :

In the given sum the solution is:

the value of x=-2

the value of y=1

Step-by-step explanation:

Given:

A system equation of A is 5x-y=-11

A system equation of B is 3x-2y=-8

Solution=-2,1

Multiply the equation A by 2

10x-2y=-22

Now substitue the Equation A and Bm

10x-2y=-22

3x-2y=-8

(-)  (+)   (+)

----------------

7x-0=-14

Therefore

7x=-14

x=-2

Substituting x=-2 in equation A to find the y Value

5x-y=-11

5(-2)-y=-11

-10-y=-11

y=-11+10

y=1

Therefore Hence the solution is proved

x=-2          y=1